Association of abdominal effusion with a single decompressive cystocentesis prior to catheterization in male cats with urethral obstruction. Issue 1 (16th December 2019) - Gerken, Katherine K.; Cooper, Edward S.; Butler, Amy L.; Chew, Dennis J.
Abstract: Objective: To evaluate the occurrence of abdominal effusion and its association with decompressive cystocentesis in male cats with urethral obstruction. Design: Prospective observational clinical study. Animals: Forty‐five male neutered, client‐owned cats with naturally occurring urethral obstruction. Procedures: Laboratory testing and point‐of‐care ultrasonography were performed. Presence of abdominal effusion was evaluated using the Focused Assessment with Sonography for Trauma (FAST) technique at presentation. Decompressive cystocentesis was then performed prior to catheterization by a standardized technique. Repeat FAST examination was performed 15 minutes after cystocentesis and the following day to further assess for the presence of abdominal effusion. Results: A mean volume of 92.3 ± 35.2 mL of urine was removed from each cat via cystocentesis prior to catheterization. At presentation, 15 of 45 (33%) had abdominal effusion (13/15 with scant effusion, 2/15 with mild), with an additional 7 cats developing scant effusion 15 minutes post‐cystocentesis. By the following day, 4 cats still had scant effusion present. No significant complications secondary to cystocentesis were reported. No association was found between severity of azotemia, or volume removed by cystocentesis, and the presence of effusion at presentation or after decompressive cystocentesis was performed. Conclusions and Clinical Relevance: A single decompressive cystocentesis prior to catheterization did not lead to development of clinically significant abdominal effusion or other discernable complications and appears to be a safe procedure in this population of patients. Abdominal effusion may be found at presentation in cats with urethral obstruction. The significance of this effusion remains to be determined.